AN ERROR ANALYSIS OF ENGLISH TENSE USAGE AMONG INDONESIAN EFL UNIVERSITY STUDENTS - Wibowo, Hermenegildus Agus; Marita Nurharjanti; Rosyidah Jayanti Vijaya (Bajang Institute, 2026)
Errors are an inevitable part of second language acquisition, particularly in the learning of grammatical features such as tense. This study aims to analyse the types and frequency of tense-related errors made by first-semester students of the Communication Science program at Amikom University Yogyakarta. Adopting a descriptive qualitative research design, data were collected from students’ short-answer tests focusing on five English tenses: simple present, present continuous, present perfect, simple past, and simple future. A total of 660 sentences produced by 33 students were analysed using error analysis procedures, including error identification, classification, and interpretation. The findings reveal that omission was the most frequent error type, accounting for 50% of the total errors, followed by misinformation (32%) and overgeneralization (18%). In terms of tense usage, errors in the simple past tense occurred most frequently (38%), followed by the simple present tense (27%), present perfect tense (27%), present continuous tense (5%), and simple future tense (3%). These results indicate that students experience significant difficulties in applying tense forms accurately, particularly those involving verb inflection and auxiliary usage. The study highlights the importance of targeted grammar instruction and suggests that systematic, error-focused teaching and remedial support may help reduce persistent tense errors and enhance learners’ grammatical accuracy.